2022
DOI: 10.3233/jvr-211171
|View full text |Cite
|
Sign up to set email alerts
|

Treatment and provider choice in worker injury rehabilitation: A systematic literature review

Abstract: BACKGROUND: In the face of significant costs for injured worker rehabilitation and its impact on society, ongoing examination of how rehabilitation is carried out is warranted. OBJECTIVE: To review recent studies that explored the impact of the worker’s choice in terms of provider and treatment on the outcome for the worker in injury rehabilitation. METHOD: A systematic literature review was conducted using searches through electronic databases, with studies retrieved then subjected to a quality appraisal. RES… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 36 publications
(42 reference statements)
0
1
0
Order By: Relevance
“…These ramifications, in turn, exert a profound impact not only on the injured individual but also on their employer. The profound ramifications of occupational injuries on the reintegration of workers into the workforce are undeniably noteworthy (Birtanov, 2016;Anderson, McLennan and Randall, 2022). In numerous instances, it is observed that individuals who have sustained injuries while engaged in occupational activities may encounter difficulties in resuming their previous employment or may find themselves incapacitated to engage in any form of work, thereby leading to a decline in both financial resources and overall well-being.…”
Section: Introductionmentioning
confidence: 99%
“…These ramifications, in turn, exert a profound impact not only on the injured individual but also on their employer. The profound ramifications of occupational injuries on the reintegration of workers into the workforce are undeniably noteworthy (Birtanov, 2016;Anderson, McLennan and Randall, 2022). In numerous instances, it is observed that individuals who have sustained injuries while engaged in occupational activities may encounter difficulties in resuming their previous employment or may find themselves incapacitated to engage in any form of work, thereby leading to a decline in both financial resources and overall well-being.…”
Section: Introductionmentioning
confidence: 99%